New proposals for the design of steel beam-columns under fire conditions - Lopes, Nuno (2010)
The possibility of having, in parts 1-1 and 1-2 of Eurocode 3, the same approach for the design of beam-columns and for lateral-torsional buckling, was investigated by the authors in previous papers using a numerical approach, where it was concluded that those assumptions could be made. In the present paper a new approach for lateral-torsional buckling has been used with the formulae for the design of beam-columns at elevated temperature based on prEN 1993-1-1 combined with the formulae from prEN 1993-1-2. In both cases the results obtained are much better than the current design expressions, when compared with those obtained in the numerical calculations.